The Influence of Education, Training and Work Experience on Employee Competence at Mall X in Bandung City - Fauzzia, Willma; Komara, Endang; Syarifuddin, Didin (Business Management, 2026)
This study aims to analyze the influence of education, training, and work experience on employee competence at Mall X in Bandung City. The research employs a quantitative method with a descriptive and verificative approach. The population consists of 110 active employees at Mall X, utilizing a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS version 19. The results indicate that: (1) education has a negative and significant effect on employee competence (t-value = 9.517, p < 0.05); (2) training has a positive and significant effect on employee competence (t-value = 23.218, p < 0.05); (3) work experience has a positive and significant effect on employee competence (t-value = 7.153, p < 0.05); and (4) simultaneously, education, training, and work experience significantly influence employee competence (F-value = 384.034, p < 0.05) with a coefficient of determination (R²) of 91.6%. These findings suggest that while formal education may not directly enhance competence in hard service operations, structured training programs and accumulated work experience significantly contribute to employee competence development in the retail industry.